DETERMINAN PERILAKU BELI PRODUK HIJAU - Nur Jannah Eka Rachmawati; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to examine the effect of consumer’s purchase intention and the behaviour. Customer’s purchase intention has some factors. The factors are green product knowledge, perceived consumer effectiveness, perceived price, and green trust. The high consumer’s purchase intention affects the consumer behaviour. The data collect by using questionnaires for the green customers in Surakarta with cluster. The sample collection was taken from 200 respondents. This analysis uses Structural Equation Modelling (SEM), moderate regress analysis and logistic regress analysis. The result of the sudy shows that customer’s purchase intention give the positive effect of their behaviour, green trust gives the positive effect of purchas e intention, perceived cnsumer effectiveness gives the positive effect of purchase intention, perceived price does not moderate the rellation between green trust and purchase intention, green product knowledge gives the possitive effect of green trust, and green product knowledge gives the positive effect to the perceived consumer effectiveness